Assessing Mango Fruit Value Chain in Bangladesh: Mango Value Chain in Bangladesh (SAARC Journal of Agriculture, 2022)
Addressing the systemic constraints is very important for the economics of mango production in Bangladesh, which is the 7th largest mango producing country in the world. Based on the functions any value chain includes three function actors and different dimensions such as inclusiveness (i.e., extreme poor inclusion) and gross margin, the study qualitatively and quantitatively assessed mango fruit value chain. Methodologies were applied with an assemblage of bottom-up and top-down approaches. Structured questionnaires were used to survey mango producing households, input sellers and mango buyers. The percentile value of composite revealed that mango fruit production and selling the annual specified gross margin (SGM) were Tk.1,600 (66%) for extreme poor (hereafter referred to as EP) producers, while Tk.1,09,880 (64%) for rich producers and Tk. 2,43,000 (76%) for retailers/middleman. The profit margin of medium and rich producers as well as middlemen was better, but less for poor and EP households due to the systemic market constraints. This assessment aims to prepare improving strategies and/or interventions for mango production that elucidates what actions could be taken for the mango fruit value chain in different segments such as improved technologies, harvesting, grading, packaging, transportation, marketing, etc. so that the poor and EP households will get more profit margin from mango production.SAARC J. Agric., 20(1): 227-238 (2022)